Dietary Organic Acids Modulate Gut Microbiota and Improve Growth Performance of Nursery Pigs - Xiaoyuan Wei; Kristopher A. Bottoms; Hans H. Stein; Laia Blavi; Casey L. Bradley; Jon Bergstrom; Joshua Knapp; Robert Story; Charles Maxwell; Tsungcheng Tsai; Jiangchao Zhao (Microorganisms, 2021)
Feed additives have been suggested to improve animal growth performance through modulating the gut microbiota. The hypothesis of this study was that the combination of two organic acids would exert synergistic effects on the growth performance and gut microbiota of weaning pigs. To test this hypothesis, we followed 398 weaning pigs from two university experiment stations (University of Illinois at Urbana-Champaign (UIUC) and University of Arkansas (UA)) to determine the effects of increasing levels (0%, 0.035%, 0.070%, and 0.105%) of sodium butyrate combined with 0.5% benzoic acid on the growth performance of nursery pigs. At the UA, an additional negative control diet was included and the gut microbiota analysis was carried out. At both universities, increasing levels of sodium butyrate in a diet containing 0.5% benzoic acid improved growth performance, which reached a plateau in the pigs fed 0.035% (SBA0.035) or 0.070% (SBA0.070) butyrate. Gut microbiota analysis revealed that pigs fed the SBA0.035 diet had more diverse microbiota and contained more potentially beneficial bacteria such as Oscillospira, Blautia, and Turicibacter and reduced levels of Veillonella and Sarcina. Results of the present study indicated that the inclusion of sodium butyrate at moderate levels in a diet containing 0.5% benzoic acid improved growth performance of weaning pigs and established potential health benefits on gut microbiota.